2010
DOI: 10.1002/cbic.201000201
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferases and their Assays

Abstract: Glycosyltransferases (GTs) are a large family of enzymes that are essential in all domains of life for the biosynthesis of complex carbohydrates and glycoconjugates. GTs catalyse the transfer of a sugar from a glycosyl donor to a variety of acceptor molecules, for example, oligosaccharides, peptides, lipids or small molecules. Such glycosylation reactions are central to many fundamental biological processes, including cellular adhesion, cell signalling and bacterial- and plant-cell-wall biosynthesis. GTs are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 118 publications
(152 reference statements)
0
73
0
Order By: Relevance
“…Therefore, the observed correlation between precocious or delayed endosperm cellularization with respectively decreased or increased endosperm proliferation in response to interploidy hybridizations [13,44] seems unlikely to reflect a general mechanism coupling endosperm proliferation to cellularization. Our transcriptome data revealed that endosperm cellularization failure in response to interspecies and interploidy hybridizations correlated with increased expression of enzymes that hydrolyze glycosidic bonds between carbohydrates and could therefore degrade cell walls [45]. This suggests that the timing of endosperm cellularization is transcriptionally controlled and requires suppression of cell wall degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed correlation between precocious or delayed endosperm cellularization with respectively decreased or increased endosperm proliferation in response to interploidy hybridizations [13,44] seems unlikely to reflect a general mechanism coupling endosperm proliferation to cellularization. Our transcriptome data revealed that endosperm cellularization failure in response to interspecies and interploidy hybridizations correlated with increased expression of enzymes that hydrolyze glycosidic bonds between carbohydrates and could therefore degrade cell walls [45]. This suggests that the timing of endosperm cellularization is transcriptionally controlled and requires suppression of cell wall degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of binding is unknown, and the level of inhibitory activity of this pseudodisaccharide is fairly low compared to the state of the art for glycosyl transferase inhibition. [29][30][31] Nevertheless, this result demonstrates that inhibition of this medically relevant enzyme by carbasugar derivatives is possible, and in fact, significantly better inhibitors for galactofuranosyl transferases have not been reported.…”
Section: Discussionmentioning
confidence: 48%
“…Nucleophilic substitution at the anomeric carbon of the transferred glycosyl residue proceeds with either inversion or retention of configuration of the donor substrate [16][17][18]. Glucosides of secondary metabolites found in plants normally have a b-configuration.…”
Section: Resultsmentioning
confidence: 99%